1986
DOI: 10.1002/cne.902460410
|View full text |Cite
|
Sign up to set email alerts
|

Origins of afferents to visual suprageniculate nucleus of the cat

Abstract: Small iontophoretic ejections of horseradish peroxidase (HRP) were made from recording-multibarrel micropipette assemblies in areas of the cat's suprageniculate nucleus (SGn) that contained visually responsive neurones. The sources of afferents of the SGn were determined by locating the labeled cell bodies of neurones that were presumed to send their axons to the area of the SGn containing the light-sensitive cells. The greatest concentration of labeled cell bodies was found in the granular insular cortex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 76 publications
4
20
0
Order By: Relevance
“…In this respect, our results agree well with those reported by Abramson and Chalupa (1988) and with the study of Hicks et al (1986). Earlier reports on SC efferents to other areas, such as the dorsal and ventral lateral genicu-late nucleus (Harrel et al, 1982), the superioriinferior olive Weber et al, 1978), and the pontine and other reticular structures (Hashikawa and Kawamura, 1977;Kawamura and Hashikawa, 19781, describe cells with the same size as was found in our study.…”
Section: Size and Morphological Characteristics Of Labeled Cellssupporting
confidence: 95%
See 1 more Smart Citation
“…In this respect, our results agree well with those reported by Abramson and Chalupa (1988) and with the study of Hicks et al (1986). Earlier reports on SC efferents to other areas, such as the dorsal and ventral lateral genicu-late nucleus (Harrel et al, 1982), the superioriinferior olive Weber et al, 1978), and the pontine and other reticular structures (Hashikawa and Kawamura, 1977;Kawamura and Hashikawa, 19781, describe cells with the same size as was found in our study.…”
Section: Size and Morphological Characteristics Of Labeled Cellssupporting
confidence: 95%
“…In four of the five cats used in this study , the HRP injection site was located graphic and HRP studies showing that fibers from the SC terminate in the Sg (Graham, 1977;Hicks et al, 1986;Abramson and Chalupa, 1988). In addition, however, we also found labeled neurons in the contralateral SC and in the external nuclei of the inferior colliculus (IC) on both sides.…”
Section: Resultsmentioning
confidence: 90%
“…There have been several reports of somatosensory or visual influences on neuronal activity in subcortical auditory structures (Aitkin et al 1981;Young et al 1992;Doubell et al 2003;Komura et al 2005;Shore and Simic 2005;Musacchia et al 2006). Moreover, following tracer injections in auditory cortex, we observed retrograde labeling in the suprageniculate nucleus of the thalamus, which is known to receive auditory, somatosensory, and visual inputs (Hicks et al 1986;Benedek et al 1997;Eošrdegh et al 2005). Local field potential recordings from monkey auditory belt areas have shown that somatosensory responses have a similar feedforward profile to the auditory responses, that is, beginning in layer IV and then spreading to extragranular layers (Schroeder et al 2001).…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have distinguished the MGsg based on connections with other regions of the brainstem, especially regarding strong projections to the MGsg from the superior colliculus (Tanaka et al, 1985; Hicks et al, 1986; Hoshino et al, 2010) and the sagulum (Morest, 1965). Examination of these regions in our experiments suggests that the MGsg in guinea pigs receives similar inputs.…”
Section: Discussionmentioning
confidence: 99%